L’émirat de Barqa et les Fatimides : les enjeux de la navigation en Méditerranée centrale au xie siècle - David Bramoullé (Revue des Mondes Musulmans et de la Méditerranée)
Barqa, Fatimides, Navigation, Geniza, Commerce, Jihad, Méditerranée, Banū Qurrā’, Tribus arabesIn spite of their oriental attraction and their installation in Egypt in 973, the Fatimids never lost their interests for Ifriqiya and Sicily. The Geniza letters give new informations concerning the Barqa’s area in modern Libya in the beginning of the xi th century. Unable to ensure the order themselves, the Fatimids had to put up with the settlement in the area of an uncontrollable Bedouins clan: the Banū Qurrā’ and their chiefs. They created a corsary emirate in charge of the security of the shipping lanes in the name of the Fatimids. These emirs used to get from the Fatimids caliphate an astonishing freedom of action and they played a major part in the navigation between Egypt, Ifriqiya and Sicily. They helped the Fatimids to keep their image and reputation of naval strength whereas the official fleet was quite inactive. The Barqa’s emirate actions in the central Mediterranean respond to key stakes for a caliphal dynasty in search for legitimacy and ready for everything to serve its goals.